SEJARAH LANUD ROESMIN NURJADIN PEKANBARU (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Air Force Base or the abbreviated Airbase is the area on the mainlandor in the waters with certain limits within the Republic of Indonesia that is used fortakeoff and landing of aircraft for purposes of national defense by the Indonesian AirForce. Indonesia has areas with excellent air defense, like Jakarta HalimPerdanakusuma Airbase, Bogor with Atang Sendjaja Airbase, Subangwith SuryadarmaAirbase, Pontianakwith Supadio Airbase and Pekanbaru with Roesmin NurjadinAirbase. Fifth airbase airfield is very famous in Indonesia with type A and under theunit ranks Koopsau I. Airbase led by a commander Air Base as a single unit with theIndonesian Air Force. The purpose of this study was to determine the history of theRoesmin Nurjadin Airbase Pekanbaru which became one of the best Airbase inIndonesia. The method used was descriptive method, where data were collected throughinterviews, observation, documentation, and library studies. Data was analyzed usingqualitative way. When the study began filing title until the completion of a revisedproposal last essay writer. The results showed that the air base was formerly namedRoesmin Nurjadin is Simpang Tiga Airpots which has a very long history. Based onthese results it can be concluded that the air base that was formerly named RoesminNurjadin is Simpang Tiga Airports which was first created by the Dutch government onOctober 10, 1930 with the permission of Sultan Siak Sultan Syarif Kasim II.Keywords: Airbase, Roesmin Nurjadin, Pekanbaru